Characteristics and Environmental Quality of using Tribe Settlements in Kemiren - Abu Sufyan; Tri Anggraini Prajnawrdhi; Ni Ketut Agusintadewi (Wacana Journal of Social and Humanity Studies, 2020)
Kemiren Village is designated as a traditional house architecture tourism village. The development has brought Kemiren Village to economic experienced growth and will be affecting dynamic changes of physical settlements. Research using the rationalistic-qualitative, descriptive and explorative method. Data collection conducting by field observations, interviews, and documentation then be analyzed using descriptive analysis, evaluative analysis, and development analysis approach. Results from physical conditions mapping, the characteristics of settlements are highly dependent on aesthetic quality, scarcity, and exceptionalness. Result from the analysis, the value of culture is 60%, while the value of environmental quality is 50%.Â Â